Hypothalamic-pituitary-adrenal axis activity in the comorbidity between obsessive-compulsive disorder and major depression. (July 2018) - Labad, Javier; Soria, Virginia; Salvat-Pujol, Neus; Segalàs, Cinto; Real, Eva; Urretavizcaya, Mikel; de Arriba-Arnau, Aida; Ferrer, Alex; Crespo, José M.; Jiménez-Murcia, Susana; Soriano-Mas, Carles; Alonso, Pino; et al.
Highlights: We explored the role of the HPA axis in the comorbidity between MDD and OCD. Cortisol awakening response (CAR), cortisol diurnal slope, and DST were analyzed. Multivariate analyses were adjusted for depressive and anxiety symptoms. OCD patients with comorbid MDD showed a more flattened diurnal cortisol slope. Trait anxiety influenced the relationship between OCD and HPA axis (CAR and DST). Abstract: Major depressive disorder (MDD) is the most common psychiatric comorbidity in patients with obsessive–compulsive disorder (OCD). Hypothalamic-pituitary-adrenal (HPA) axis abnormalities have been described in both disorders and might play a role in the association between them. We aimed to study the role of HPA axis activity in the comorbidity between OCD and MDD, while controlling for psychopathological dimensions such as anxiety and depressive symptoms. We studied 324 participants belonging to four diagnostic groups: 1) MDD (n = 101), 2) OCD with comorbid MDD (n = 33), 3) OCD without MDD (n = 52), and 4) healthy subjects (n = 138). State anxiety, trait anxiety and depressive symptoms were assessed. Three HPA axis measures were analyzed in saliva: cortisol awakening response (CAR), diurnal cortisol slope (calculated using two formulas: [1] awakening to 11 p.m. [AWE diurnal slope]; [2] considering fixed time points [FTP diurnal slope] from 10 a.m. to 11 p.m.), and dexamethasone suppression test ratio after 0.25 mg of dexamethasone (DSTR). Multiple linear regression analyses were conducted to explore the contribution of clinical diagnosis and symptom dimensions to each HPA axis measure. A more flattened FTP diurnal cortisol slope was observed for OCD patients with comorbid MDD. Regarding the CAR and DSTR, a significant interaction was found between trait anxiety and OCD, as OCD patients with greater trait anxiety showed an increased CAR and reduced cortisol suppression after dexamethasone administration. Our results suggest that trait anxiety plays an important role in the relationship between HPA axis measures and OCD/MDD comorbidity.